2019
DOI: 10.3389/fneur.2019.00003
|View full text |Cite
|
Sign up to set email alerts
|

Management of Hereditary Spastic Paraplegia: A Systematic Review of the Literature

Abstract: The term hereditary spastic paraplegia (HSP) embraces a clinically and genetically heterogeneous group of neurodegenerative diseases characterized by progressive spasticity and weakness of the lower limbs. There currently exist no specific therapies for HSP, and treatment is exclusively symptomatic, aimed at reducing muscle spasticity, and improving strength and gait. The authors set out to perform a comprehensive systematic review of the available scientific literature on the treatment of HSP, applying Cochra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 42 publications
0
61
0
6
Order By: Relevance
“…A recent systematic review evaluated treatment options in HSP, taking into account both pure and complicated forms. 17 Several pharmacological and physical therapies were assessed, as were intrathecal baclofen and dorsal rhizotomy. Most studies included were of low quality, the ones that were well-designed showed no significant improvement, or did not evaluate clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review evaluated treatment options in HSP, taking into account both pure and complicated forms. 17 Several pharmacological and physical therapies were assessed, as were intrathecal baclofen and dorsal rhizotomy. Most studies included were of low quality, the ones that were well-designed showed no significant improvement, or did not evaluate clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies that support the contribution of oxidative stress to neuronal death initiation and also as an to neurodegenerative process augmentation. Therefore the anti oxidative therapy (39,40) and cholesterol lowering drugs added to anti spastic therapy , K+ channel blocker drugs, levodopa therapy, folic acid therapy and other rehabilitation therapies (41,42,43,44,45,46) could constitute a future strategy for improving the quality of life for this patients.…”
Section: Discussionmentioning
confidence: 99%
“…HSP was one of the included conditions, however, no systematic reviews were identified at the time of searches. The overall literature in this condition is limited to case studies of rehabilitation interventions (61) and small studies of hydrotherapy (62) or robot gait training (63,64), as confirmed in a recent systematic review, identified subsequently to our scoping review searches (23). The authors of this recent systematic review rated the overall quality of physical interventions in HSP as low.…”
Section: Rare Diseases Under Studymentioning
confidence: 99%
“…These interventions widely comprise "Any bodily movement produced by skeletal muscles that requires energy expenditure" and any type of structured exercise (15) including gait and balance training, video-gaming (16)(17)(18) and cognitive behaviour interventions (19)(20)(21). However, although physical activities are promoted as an essential part of the clinical management across RNCs, evidence supporting physical activity interventions is still lacking in these conditions (22)(23)(24)(25)(26)(27). To date, there are significant gaps in understanding about which types of activities maintain physical functioning and increase participation in activities and quality of life across RNCs.…”
Section: Introductionmentioning
confidence: 99%